Application of biostimulant and CaO to remediate acid mine drainage on the coal mining land in Lampung Sumatra Island - Mohammad Nurcholis; Made Wijaya; Wawong D Ratminah (Brawijaya University, 2018)
Mining using an open pit system may lead to a deterioration in the quality of the environment in term of the extent of the cleared land, heavy metals contamination on the overburden rock, the formation of acid mine drainage (AMD) with a pH <5, high level of total suspended solid (TSS), and the content of the metal on it. Several research results on post-mining land indicated a change in the environmental quality of the mine. Handling of the AMD problem can be conducted by several methods, including the active method by spreading calcium oxide (CaO) in AMD with the aim of increasing pH to neutral. The purpose of this study was to study the alternative techniques to manage the AMD using biostimulant. The present study was conducted firstly in the vinil house by using 10 L of AMD water sample with 2 kinds of treatment, i.e. CaO with levels of 0.2 and 0.25. Biostimulant with four kinds of treatment (I, II, III and IV) which resulted from the combination of different types of biostimulants (A, B and C) with different in composition. Secondly, research on the 1000 L of AMD for scaling up applications in the field. CaO and Biostimulant doses were obtained from the first stage of the study. Analysis pH, TSS, Fe, and Mn of the AMD were done on the control, CaO, and biostimulant treatments. CaO treatment resulted in an increase in pH to 6.9, TSS decreased significantly decline so to 60 mg/L. Fe content in AMD decreased to 0.22 mg/L, and Mn levels decreased to 0.12 mg/L on day 10. Biostimulant treatment resulted in increase of pH to pH 6.7. The TSS value decreased to 40 mg/L. Fe and Mn levels decreased to 0.03 mg/L and Mn 2.98 mg/L, respectively.